A randomized trial of prophylactic palifermin on gastrointestinal toxicity after intensive induction therapy for acute myeloid leukaemia. (21st August 2014) - Bradstock, Kenneth F.; Link, Emma; Collins, Marnie; Di Iulio, Juliana; Lewis, Ian D.; Schwarer, Anthony; Enno, Arno; Marlton, Paula; Hahn, Uwe; Szer, Jeff; Cull, Gavin; Seymour, John F.; et al.
Summary Gastrointestinal toxicity, including oral mucositis, is a frequent complication of intensive combination chemotherapy for acute myeloid leukaemia (AML) and contributes substantially to treatment‐related mortality. We conducted a placebo‐controlled randomized trial to evaluate the efficacy of palifermin (keratinocyte growth factor), given at 60 μg/kg per daily IV for 3 d before and after chemotherapy, for mucosal protection in adult patients with previously untreated AML receiving induction therapy with idarubicin, high‐dose cytarabine and etoposide. Among 155 randomized patients, there was no statistically significant difference in the rate of grade 3 and 4 oral mucositis (primary study endpoint) between the two treatment arms (three in palifermin arm (4%), 8 in placebo arm (10%; P = 0·21); however, when considering the severity of oral mucositis (World Health Organization grade 0–4), there was evidence of reduced rates of higher grades of oral mucositis in the palifermin arm (P = 0·0007, test for trend). There was a statistically significantly lower rate of grades 3 and 4 gastrointestinal adverse events in the palifermin arm (21% vs. 44% in placebo arm; P = 0·003), mainly due to a reduction in severe diarrhoea (8% palifermin, 26% placebo; P = 0·01). Palifermin has activity as a mucosal protectant in AML patients receiving intensive chemotherapy. This trial is registered at ACTRN012605000095662.